2012
DOI: 10.1259/dmfr/82622690
|View full text |Cite
|
Sign up to set email alerts
|

Web-based calibration of observers using MRI of the temporomandibular joint

Abstract: Objectives: Research diagnostic criteria for temporomandibular disorders (RDC/TMDs) were proposed in 1992 with the aim of standardizing and testing methods for diagnosing TMDs. RDC/TMDs have so far been lacking standardized methods for imaging and criteria for imaging diagnosis of disorders of the temporomandibular joint (TMJ). Criteria for disorders of the TMJ have recently been proposed for MRI. The aim of this study was to publish MR images of the TMJ on the web and to test the agreement of five observers u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…In the present cases, the anterior disc fragment was distinguished from the lateral pterygoid muscle using serial MR images. The differential diagnosis Fracture of the articular disc in the TMJ for a low signal intensity within the TMJ includes calcified loose bodies, synovial chondromatosis or chondrocalcinosis; 16 however, these structures are usually evident as a calcification on plain radiography, which was not observed in the present cases. Based on the imaging and clinical findings, the present two cases were diagnosed as disc fracture, even though arthroscopic and surgical confirmation was not performed.…”
Section: Discussioncontrasting
confidence: 54%
“…In the present cases, the anterior disc fragment was distinguished from the lateral pterygoid muscle using serial MR images. The differential diagnosis Fracture of the articular disc in the TMJ for a low signal intensity within the TMJ includes calcified loose bodies, synovial chondromatosis or chondrocalcinosis; 16 however, these structures are usually evident as a calcification on plain radiography, which was not observed in the present cases. Based on the imaging and clinical findings, the present two cases were diagnosed as disc fracture, even though arthroscopic and surgical confirmation was not performed.…”
Section: Discussioncontrasting
confidence: 54%
“…Since the criteria are valid and reliable tool and are accepted internationally, therefore, it could help to provide knowledge in a standardised way. Hellen‐Halme et al 20 and our research team in the previous study 18 reported the usefulness of using Ahmad et al 8 criteria. Both teams assumed that it could increase the diagnostic outcome among observers for magnetic resonance imaging (MRI) and CBCT evaluations of the TMJ, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…A similar performance was observed in the second assessment by 80% correct diagnosis, which could suggest that they reasonably grasp the presented knowledge without a noticeable improvement; therefore, they may need more practice. Hellen‐Halme et al 20 developed a comparable web‐based programme for examining soft tissue changes in the TMJ using MRI and following Ahmad et al 8 criteria.…”
Section: Discussionmentioning
confidence: 99%
“…A study comparing MRIs of TMJ showed significantly better image quality as well as visibility and delineation of clinically relevant anatomical structures obtained at 3.0 T than at 1.5 T. In addition, the interrater reliability ranged from "substantial agreement" to "almost perfect agreement." [17] Several approaches have addressed the issues around the reliability of TMJ MRI, which include the adoption of preestablished criteria, [11,[18][19][20] observer calibration, [21] the use of techniques to quantify joint disk position, [22] and digital tools. [23] These methods went no further than producing a moderate agreement in interpretation.…”
mentioning
confidence: 99%